Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1746-1049.2008.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro and Small Enterprise Growth in Turkey: Under the Shadow of Financial Crisis

Abstract: The present study analyzes the impacts of selected factors on the growth of micro and small enterprises (MSE) in Turkey. Using unique national field survey data on urban MSE that engage 1-49 persons, we present the determinants of MSE growth for the period between the start-up of enterprises and the year 2000. We evaluate the impact of the financial crisis experienced in Turkey in 2001 on MSE. Detrimental effects of the crisis on MSE are clearly detected in our estimations. Some of the factors contributing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…According to [15], small enterprises support functional and competitive markets as agents of income distribution, industrial expansion and poverty reduction. The owner manager's failure to plan, manage and control the business activities has contributed to the low sustainability of these enterprises [16] [17].…”
Section: Small Enterprises Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [15], small enterprises support functional and competitive markets as agents of income distribution, industrial expansion and poverty reduction. The owner manager's failure to plan, manage and control the business activities has contributed to the low sustainability of these enterprises [16] [17].…”
Section: Small Enterprises Developmentmentioning
confidence: 99%
“…Accounting professionals should be more involved in small enterprises to assist in prudent accounting processes [2]. A study by [15] found that small enterprises development increased wealth generation, jobs creation and improved economic and social conditions of a nation. Formal and informal small enterprises contributed more than 18.4 percent of Kenya's GDP with most comprising of retail, mining and quarry, agriculture, manufacturing, service/finance and other sub-sectors of the economy [18].…”
Section: Small Enterprises Developmentmentioning
confidence: 99%
“…SMEs may suffer disproportionately from economic downturns, because of their limited financial resources and dependence on banks' lending, paying such high interest rates (Mulhern [13] for the crisis of 1989-1994 in Venezuela, Domac¸ and Ferri [14] for the 1997 Asian financial crisis and Ozar et al [15] for the 2001 Turkish financial crisis). Adding to the financial aspect, their relative shortcomings in terms of technological, managerial and human capabilities may reduce their capacity to overcome the economic crisis [16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 98%
“…According to Ozar et al (2008) there has been a growing interest and attention in the role small enterprises play in the economy since the 1980s. One of the reasons for this considerable attention is that these enterprises have been found to have potential to generate employment and also to contribute to poverty alleviation in most countries in sub-Saharan Africa where social environments have worsened overtime due to increasing levels of unemployment as well as increasingly widening gaps of income inequality.…”
Section: Characteristics Of Small and Micro Enterprisesmentioning
confidence: 99%